Differences in Xylan Degradation by Various Noncellulolytic Thermophilic Anaerobes and Clostridium thermocellum - Wiegel, Jürgen (1985)
Hemicellulose fractions with a predetermined distribution of xylose, xylooligomers, and xylan fractions were obtained through steam explosion of wood by the steam explosion-extraction process of BFA-Hamburg, Hamburg, Federal Republic of Germany. A differential utilization of various molecular-weight fractions by several thermophilic anaerobic bacteria was determined during their growth on the hemicellulose preparations. Clostridium thermocellum (60°C) first utilized the high-molecular-weight fractions (polymerization degree of 15 to 40 xylose units). Xylose and xylooligomers of n = 2 to 5 accumulated while C. thermocellum was not growing, as evident from the fermentation products formed. Whereas the xylan was hydrolyzed and the small oligoxylans were utilized after more than 100 h of incubation, xylose was not significantly utilized. In contrast to this, C. thermohydrosulfuricum (70°C) and Thermoanaerobium brockii (70°C) utilized xylose first and then xylooligomers of n = 2 to 5, but xylooligomers of n greater than 6 were only slowly utilized. Thermoanaerobacter ethanolicus (70°C), Thermobacteroides acetoethylicus (70°C), and C. thermosaccharolyticum (60°C) utilized xylose preferentially. Xylooligomers of n = 2 to 5 and n = 6 and greater were apparently concomitantly utilized without significant differences. In contrast to C. thermocellum, the non-cellulolytic organisms grew during xylan hydrolysis, producing ethanol, lactate, acetate, CO(2), and H(2).